PD-1 inhibitors in advanced esophageal squamous cell carcinoma: a survival analysis of reconstructed patient-level data - Yan, Chunyan; Cao, Wenxiu; Li, Jianghua; Zhang, Lei; Diao, Ruigang (Frontiers in Pharmacology, 2024)
Background: Recently, a sum of trials of programmed cell death-1 (PD-1) inhibitors combined with chemotherapy have showed excellent efficacy compared to chemotherapy alone in patients with previously untreated, advanced esophageal squamous cell carcinoma (ESCC). However, there is no head to head comparison and consensus on which immunotherapy regimen results in better survival outcome. This study was aimed to evaluate the survival efficacy of various PD-1 inhibitor based therapies in the first-line treatments for advanced ESCC patients. Methods: Data were collected prior to July 31, 2023 were searched in the Pubmed, Cochrane Library, Embase, Medline and Web of Science databases. overall survival (OS) and progression-free survival (PFS) curves were pooled using the MetaSurv package. Survival data were compared by reconstructed individual patients data (IPD). Results: A total of 4,162 patients and seven randomized controlled trials (RCTs) were included. After synthesizing, PD-1 inhibitors prolonged median OS from 11.3 months (95% CI (Confidence interval) 10.7-11.7) to 15.6 months (95% CI 14.7-16.3). Based on reconstructed patient-level data, toripalimab, tislelizumab and sintilimab groups achieved the longest OS, while sintilimab and tislelizumab group performed lower risk of recurrence than other treatments. In patients with combined positive score (CPS) ≥10, sintilimab had better OS efficacy than pembrolizumab (HR(hazard ratios): 0.71, 95% CI: 0.52-0.96). In terms of tumor proportion score (TPS) ≥1%, camrelizumab, nivolumab and toripalimab showed proximate survival benefits in both OS and PFS. Conclusion: PD-1 inhibitor combined with chemotherapy significantly improved the survival time of advanced ESCC patients. Toripalimab, tislelizumab, and sintilimab plus chemotherapy performed the best OS benefit. Longer progress-free benefit might be generated from adding tislelizumab, and sintilimab to chemotherapy. Sintilimab was strongly recommended to patients with high programmed cell death-Ligand 1 (PD-L1) abundance.